ANALISA KEBIJAKAN PEMERINTAH KOTA BATAM TERKAIT ANCAMAN PENGANGGURAN PASCA KENAIKAN INFLASI - Winna Angelina; Nicholas Sunaidi; Vina Sonata; Jackson Jackson; Jason Jason; Hery Haryanto (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
The inflation and the unemployment rate can be used as benchmarks for whether a region's economy is good or bad. This study aims to analyze how the government's policies related to the threat of unemployment after rising inflation. The object used in this study is Batam City and analyzed using secondary data from 2017 – 2022 obtained from BPS and other supporting sources. From the results of this analysis, it is known that the unemployment rate in Batam City has been handled quite well due to a decrease although overall it is still high. Meanwhile, the inflation rate in Batam City is also in the good category and can still be controlled. Therefore, it can be concluded that the inflation rate can affect the rise and fall of the unemployment rate accompanied by certain other factors.